PREVALENCE OF GASTROINTESTINAL AND BLOOD PARASITE IN BREEDING CATTLE AT INTEGRATED PALM OIL PLANTATION IN CENTRAL KALIMANTAN PROVINCE - Riadini, Aprilia Rizky; Kristanto, Dwi (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2025)
Cattle raised on palm oil plantations are susceptible to parasitic infections due to environmental conditions, necessitating regular health monitoring by governmental veterinary authorities. These infections pose significant health risks, affecting cattle welfare and leading to economic losses such as diminished reproductive efficiency, reduced milk production, and weight decline. A study conducted in Pangkalan Lada, Central Kalimantan, examined parasitic infections in cattle managed by an integrated palm oil company. Sampling efforts began in 2017, with 72 fecal and 72 blood smear samples submitted to the Balai Besar Veteriner Banjarbaru in South Kalimantan. Subsequent years saw 147 fecal and 135 blood smear samples collected in 2018 and 76 fecal and 91 blood smear samples in 2019. Fecal samples were randomly collected from the rectum, while blood samples were drawn from the coccygeal vein. Disease prevalence was calculated using the formula: prevalence = (number of cases) / (population at risk). The study focused on gastrointestinal parasites (Trichostrongylus sp., Oesophagostomum sp., Eimeria sp., Cooperia sp.) and blood parasites (Babesia sp., Theileria sp.). Results revealed peak gastrointestinal parasitism in 2018, while blood parasitism was highest in 2017. These findings underscore the need for ongoing health management in cattle within plantation systems.